1998
DOI: 10.1159/000015040
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome identification in human oocytes and polar bodies by spectral karyotyping

Abstract: Sixty unfertilized human oocytes and two fresh polar bodies were karyotyped by spectral karyotyping (SKY). The oocytes were provided by 29 women ranging from 30 to 42 yr of age. The mean hybridization efficiency for oocytes was 95.2% (60/63). Nondisjunction of bivalent chromosomes (13.3%) and predivision of sister chromatids at meiosis I (3.3%) were unequivocally determined by analysis first with SKY and then fluorescence in situ hybridization. Four oocytes (6.7%) were hyperhaploid, six (10.0%) were hypohaploi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
38
0
2

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(41 citation statements)
references
References 24 publications
(60 reference statements)
1
38
0
2
Order By: Relevance
“…Instead, single chromatids, defined as resulting from a precocious division of the centromere during anaphase I, constituted the only abnormality (Angell, 1997). Other investigators, however, provided evidence for the existence of both mechanisms (Kamiguchi et al, 1993;Má rquez et al, 1998;Nakaoka et al, 1998). We have recently suggested a uniform nomenclature for oocytes with predivided chromosomes (Rosenbusch and Schneider, 2000) and, whilst reviewing the literature, noted that there is no survey of the distribution of nondisjunction and predivision in aneuploid cells.…”
mentioning
confidence: 99%
“…Instead, single chromatids, defined as resulting from a precocious division of the centromere during anaphase I, constituted the only abnormality (Angell, 1997). Other investigators, however, provided evidence for the existence of both mechanisms (Kamiguchi et al, 1993;Má rquez et al, 1998;Nakaoka et al, 1998). We have recently suggested a uniform nomenclature for oocytes with predivided chromosomes (Rosenbusch and Schneider, 2000) and, whilst reviewing the literature, noted that there is no survey of the distribution of nondisjunction and predivision in aneuploid cells.…”
mentioning
confidence: 99%
“…Instead, single chromatids, defined as resulting from a PCD during anaphase I, constituted the only abnormality (Angell, 1997). Other investigators, however, provided evidence for the existence of aneuploid oocytes with extra or missing whole chromosomes and chromatids, leading to the theory that both mechanisms, nondisjunction of bivalent chromosomes as well as unbalanced predivision of chromatids can result in numerical chromosomal abnormalities (Kamiguchi et al, 1993;Dailey et al, 1996;Má rquez et al, 1998;Nakaoka et al, 1998;Mahmood et al, 2000;Rosenbusch et al, 2001;Pellestor et al, 2002Pellestor et al, , 2003Sandalinas et al, 2002). To distinguish between these two processes, it is necessary to differentiate between whole chromosomes and single chromatids.…”
Section: Discussionmentioning
confidence: 99%
“…The frequency of chromosomal aberrations determined by these oocytes varies widely. Má rquez et al (1998) summarized data of nine studies and reported frequencies ranging from 8.1 to 59.6 %, including 7.0 % hyperhaploidies, 10.2 % hypohaploidies, 17.8 % diploidies, and 5.6 % structural aberrations. Because of the strong condensation of meiotic chromosomes in human oocytes, only a few studies were performed using cytogenetic banding techniques to precisely classify the chromosomes (Martin et al, 1986;Djalali et al, 1988;Pellestor and Séle, 1988;Ma et al, 1989;Pellestor, 1991;Pellestor et al, 2002Pellestor et al, , 2003.…”
mentioning
confidence: 99%
“…This is clearly demonstrated in FISH studies involving 6 to 9 chromosomes, where the percentage of analyzable slides decreased to some 61 % (Anahory et al, 2003;Gutierrez-Mateo et al, 2004a;Pujol et al, 2003). With the use of multicolor-FISH (M-FISH; Clyde et al, 2003), spectral karyotyping (SKY; Marquez et al, 1998;Sandalinas et al, 2002) or centromeric multicolor FISH (cenM-FISH; Gutierrez-Mateo et al, 2005), which enable simultaneous analysis of all 23 chromosomes, the percentage of useful specimen preparations decreases to mere 31-36 %. From the single cell analysis point of view, this low efficiency is inacceptable for clinical use.…”
Section: Oocyte Pb1 or Blastomere Fixationmentioning
confidence: 99%